Kewenangan Majelis Pengawas Notaris Dalam Pencegahan Terjadinya Pelanggaran Kewenangan Dan Tugas Jabatan Notaris - Ratna Madyastuti (Lex Renaissance, 2020)
This study aims to analyze the form of supervision carried out by the Notary Supervisory Council (MPN) on Notaries who carry out their positions to prevent violations of the authority of the Notary's office and to analyze differences in the authority of the Notary Supervisory Council and the Notary Honorary Council (DKN) in regards to the public reports suspected violations of Code of Ethics carried out by the Notary. This is an empirical juridical legal research, namely on the enactment or implementation of normative legal provisions on real behavior in every legal event that occurs in society. The results of the research conclude that the supervision carried out by the MPN to prevent violations of the notary's position is by holding hearings on notary, holding a meeting once a month attended by the Regional Supervisory Council (MPD) to provide directions to implement UUJN and the Code of Ethics and MPD to pay visits to the Notary's office at least once a year to check on the Notary protocol. Whereas the Notary Code of Ethics is a regulation that applies to members of the Notary's organization, if there is a violation of the Notary's Code of Ethics, the Notary's organization through DKN is obliged to examine the Notary and hold a hearing on the examination of the violation.